2022
DOI: 10.1001/jamaoto.2022.0003
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Oral Cavity Cancer Outcomes Prediction Score Incorporating Patient-Derived Xenograft Engraftment

Abstract: IMPORTANCE Patient-derived xenografts (PDXs) offer the opportunity to identify patients with oral cavity squamous cell carcinoma (OSCC) who are at risk for recurrence and optimize clinical decision-making.OBJECTIVE To develop and validate a prediction score for locoregional failure (LRF) and distant metastases (DM) in OSCC that incorporates PDX engraftment in addition to known clinicopathological risk factors. DESIGN, SETTING, AND PARTICIPANTS In this retrospective cohort study, PDX models were generated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…[8][9][10][11][12] noted correlations between clinicopathologic features of tumors and ability to form PDX, where engraftment correlates with a more aggressive phenotype. [24][25][26][27][28][29][30][31][32][33] In a small retrospective study, we reported that the ability of primary breast tumors to engraft as PDX was predictive of OS. 15 These observations motivated the TOWARDS clinical trial (Towards Personalized Medicine-Patient-Derived Breast Tumor Grafts as Predictors of Relapse and Response to Therapy, a Double Blinded Study), in which we tested whether PDX engraftment could prospectively predict disease recurrence in patients with newly diagnosed estrogen receptor (ER)-low or ER-negative breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] noted correlations between clinicopathologic features of tumors and ability to form PDX, where engraftment correlates with a more aggressive phenotype. [24][25][26][27][28][29][30][31][32][33] In a small retrospective study, we reported that the ability of primary breast tumors to engraft as PDX was predictive of OS. 15 These observations motivated the TOWARDS clinical trial (Towards Personalized Medicine-Patient-Derived Breast Tumor Grafts as Predictors of Relapse and Response to Therapy, a Double Blinded Study), in which we tested whether PDX engraftment could prospectively predict disease recurrence in patients with newly diagnosed estrogen receptor (ER)-low or ER-negative breast cancer.…”
Section: Introductionmentioning
confidence: 99%